Interpreting the changeable meaning of hashtags: Toward the theorization of a model - La Rocca, Gevisa; Boccia Artieri, Giovanni (Frontiers in Sociology, 2023)
This study contributes to the international debate on the hashtag’s nature and characteristics and attempts to define it as a relational social form affected by morphogenetic–morphostatic processes. To develop this interpretative proposal, this study uses the dimensions of time and agency, drawing on Twitter hashtag studies. Subsequently, the article recalls elements of cultural morphogenesis, traces the points of contact between hashtag studies and cultural morphogenesis, constructs an interpretative proposal of the hashtag as a relational social form, and arrives at the formalisation of a model for analysing the changing meaning of hashtags.